Síntese, caracterização e aplicação biológica de complexos derivados de bismuto(III) com ligantes do tipo aroiltioureias - Oliveira, Marcielli Indiara de (2020)
This work describes the synthesis, structural characterization and biological applications of four new bismuth(III) compounds with aroylthioureas as ligands: 1 - [Bi(La-O,S)3(HLa-S)], 2 - [Bi2(Lb-O,S)4(-Lb-12O,S,2S)2]2(C3H6O), 3 - [Bi2(Lc-O,S)2(OMe)(NO3)(H2O)]∞ and 4 - [Bi6(-Ld)6(3-NO3)2(6-NO3)](NO3)34H2O, where HLa = N-benzoyl(N’,N’-diethylthiourea), HLb = N-benzoyl(N’,N’-morpholylthiourea), H2Lc = N,N’-isoftaloilbis(N’’,N’’-dietiltioureia) and H2Ld = 2,6-dipicolinoyl(N,N-diethylthiourea). The pro-ligands HLa and HLb are considered monopodal, while H2Lc and H2Ld are bipodal. All compounds were characterized by melting point determination, Fourier-transform infrared spectroscopy (FTIR), hydrogen and carbon-13 nuclear magnetic resonance spectroscopy (NMR), mass spectrometry (MS), elemental analysis (EA) and single crystal X-ray diffraction (SC-XRD), except compound 3, which was not possible to have its structure determinated by SC-XRD. Compound 1 is a heptacoordinated mononuclear complex with three anionic chelating O,S La ligands and a neutral monopodal HLa ligand S. Compound 2 is a binuclear complex with four terminal anionic O,S Lb ligands and two bridging Lb ligands. For compound 3, a coordination polymer structure is suggested, while compound 4 behaves as a hexanuclear cluster with the anionic ligands Ld intercalating the metal centers in a complex coordination environment.The pro-ligands, the new complexes and the Bi(NO3)35H2O salt had their biological activities evaluated against antimicrobial activity in E. coli (ATCC 25922), S. aureus (ATCC 25923) and P. aeruginosa (ATCC 27853). The in vitro disk-diffusion (DD) method showed the ability of compound 2 to inhibit two types of bacteria (P. aeruginosa and S. aureus). In the results of minimum inhibitory concentration (MIC), all compounds showed significant activity against the tested bacterias except for compound 1. Yet, compound 2 was more efficient. However, the inorganic salt showed only activity against P. aeruginosa and the ligands showed no apparent activity. Therefore, the cooperative effect of the coordination of bismuth(III) and the presence of the heterocyclic ring of morpholine in compound 2 causes a remarkable increase in antimicrobial activity. These factors may be decisive for the study of new antimicrobial compounds for a possible replacement of commercially available drugs.